Community Service: Digital Accounting and Digital Marketing Training for MSMEs in Desa Baru, Pancur Batu District - Nadapdap, Kristanty M.N; Normi, Siti; Sumarsan, Thomas; Saragih, Rintan Br.; Sihite, Duma; Sagala, Farida; Ginting, Mitha C; Melianna, Saur; Gultom, Robinhot; Sianturi, Jeudi A.T.P (Jurnal Pengabdian Masyarakat Bestari, 2024)
This Community Service Program aims to improve the competitiveness of MSMEs in Desa Baru, Pancur Batu District through digital marketing training and accounting digitalization. This training equips participants with the skills to utilize online platforms and social media in product marketing, as well as using digital accounting software for more efficient and accurate financial management. The results of this program show an increase in participants' understanding of the use of digital technology in managing their businesses, which has a positive impact on operational efficiency and increasing market reach. MSMEs in this village are now better prepared to adapt to technological developments and the ever-growing digital market.